2015
DOI: 10.1016/j.rbr.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de disfunção sexual entre pacientes acompanhadas na coorte Brasília de artrite reumatoide inicial

Abstract: The prevalence of sexual dysfunction found in this study was higher than that reported in the literature in healthy women. A knowledge of the extent of the problem is needed to provide adequate therapeutic options for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
1
9
1
1
Order By: Relevance
“…This implies that those with better mobility are more likely to successfully integrate into social support networks, maintain good interpersonal relationships, require less help from others in daily activities, and have better sexual function. This finding, however, differed from some other reports [ 10 , 14 ]. This inconsistency may be attributed to the differences in age distribution of study subjects or the use of different statistical analyses.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This implies that those with better mobility are more likely to successfully integrate into social support networks, maintain good interpersonal relationships, require less help from others in daily activities, and have better sexual function. This finding, however, differed from some other reports [ 10 , 14 ]. This inconsistency may be attributed to the differences in age distribution of study subjects or the use of different statistical analyses.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of our multivariate analysis indicated that older age correlated positively with FSD, in agreement with previous findings [ 8 , 10 , 11 , 14 ]. In general, as females get older, hormone production is lower, and this may cause epithelial atrophy, decline of physical strength, and vaginal dryness, all of which can provoke dyspareunia and decreased libido [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…With regard to fertility in RA as reported in other reports, 113 a recent study observed unexplained subfertility and anovulation in 48% and 28%, respectively, of 178 women. 114 Moreover, RA itself impairs the sexual function in up to 70% of women, 115 with a direct correlation with the disease activity. 116 Both fertility status and sexual function in males have been poorly investigated, with inconclusive results.…”
Section: Fertility and Sexuality In Ra Patients Treated With Biologicmentioning
confidence: 99%